Analytical and experimental investigation on bond behavior of CFRP-to-stainless steel interface. (15th March 2019) - Tang, Hongyuan; Deng, Xuezhi; Lin, Zhinbin; Zhou, Xiang
Abstract: Steel structures using stainless steel are recently accepted as more sustainable and durable systems. Although much research has been conducted on steel structures strengthened by carbon fiber-reinforcement polymer (CFRP) material, these steel structures are often made of conventional mild steel and thus existing prediction and analysis specified for mild steel cannot be directly extended for that of stainless steel. Therefore, this study aims to develop a new prediction model for determining the bond behavior of CFRP-to-stainless steel. Load time-history bond behavior was formulated in a piecewise manner to account for varying elastic, elastoplastic and debonding stages. A total of 22 stainless steel plates bonded with CFRP laminates were fabricated and tested to calibrate the model and further quantify the critical design parameters, including layers and anchorage length. Observation of the experiment showed that debonding failure between the adhesion layer and the CFRP sheets was dominant, partially suggesting the linear stress-strain relation for the CFRP and stainless steel. Comparison of results predicted by the proposed model to the test ones demonstrated that the proposed model has a high accuracy in prediction of bond stress and bond strength.